Geochemical and surface sediment characteristics in Tanjung Lumpur mangrove, Kuantan, Pahang, Malaysia - Nurulnadia Mohd Yusoff (Kulliyyah of Science, International Islamic University Malaysia, 2010)
Sediment was chosen in present study because it can act as a major pollutant reservoir for heavy metals. The concentrations of heavy metals were studied in two periods which are non-monsoon and monsoon seasons. The amount of organic carbon and sediment characteristics were also measured in Tanjung Lumpur Mangrove that is located in urban area of Kuantan town. While, artificial markers were placed in each sampling points and measured monthly. The sediment samples were analyzed for heavy metal content using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) and the mean concentrations were as follows: Al (3.20 ± 1.06 μg/g dry weight), Cd (0.09 ± 0.02 μg/g dry weight), Co (3.15 ± 1.44 μg/g dry weight), Cr (19.9 ± 5.32 μg/g dry weight), Cu (26.6 ± 8.33 μg/g dry weight), Fe (1.02 ± 0.17 μg/g dry weight), Li (17.09 ± 5.93 μg/g dry weight), Mn (138 ± 29.60 μg/g dry weight), Ni (27.9 ± 7.73 μg/g dry weight), Pb (32.7 ± 6.29 μg/g dry weight) and Zn (46.8 ± 7.51 μg/g dry weight). The percentage of organic carbon was determined by Wet Dichromate Titration method with the mean values of 1.34 ± 0.16 %. Sediment characteristics were determined using particle size analyzer and the cumulative data was calculated to gather the average of mean size value; 6.15 ± 0.33 Ø, the average of sorting value; 2.94 ± 0.27 Ø and the average of skewness; 0.011 ± 0.007 Ø. Meanwhile, the sedimentation rate was measured to be 0.6 cm per year. According to pollution indices, the present study reveals that the heavy metals concentration in Tanjung Lumpur Mangrove's sediment were relatively low except for lead which is proven to significantly enrich at study area.